Purification and characterization of a thermostable alpha-amylase from Bacillus stearothermophilus - Chakraborty, K; Bhattacharyya, B K; Sen, S K (Folia microbiologica, 2000)
A soil isolate of Bacillus stearothermophilus was found to synthesize thermostable alpha-amylase. The enzyme was purified to homogeneity by ammonium sulfate fractionation and IECC on DEAE-cellulose column. The purified enzyme was considered to be a monomeric protein with a molar mass of 64 kDa, as determined by SDS-PAGE. The enzyme showed a wide range of pH tolerance and maximum activity at pH 7.0. The temperature tolerance was up to 100 degrees C with more than 90% catalytic activity; the maximum activity was observed at 50 degrees C. Divalent metal ions exhibited inhibitory effect on the enzyme activity. However, proteinase inhibitor did not react positively.
Keywords: Electrophoresis, Polyacrylamide Gel; teplota; Soil Microbiology; koncentrace vodíkových iontů; elektroforéza v polyakrylamidovém gelu; Geobacillus stearothermophilus; Temperature; alpha-Amylases; půdní mikrobiologie; Hydrogen-Ion Concentration; alfa-amylasy